2011
DOI: 10.1007/s00774-011-0280-x
|View full text |Cite|
|
Sign up to set email alerts
|

Burden of osteoporosis in adults in Korea: a national health insurance database study

Abstract: We evaluated the number of osteoporosis patients under treatment and secular trends in 2005-2008 in South Korea. We investigated nationwide data regarding the number of osteoporosis patients under treatment in South Korea using data from the Health Insurance Review and Assesment Service (HIRA), which includes nationwide information [corrected]. Reimbursement records from the HIRA database between 1 January 2004 and 31 December 2008 were investigated. Patients aged ≥30 years old with osteoporosis were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 11 publications
0
66
0
Order By: Relevance
“…The high morbidity and mortality of these diseases can intensify both individual and governmental financial burdens. 2,3 In 2010, in a position statement regarding osteoporosis management in postmenopausal women, The North American Menopause Society reported that weight-bearing exercise, which could be as simple as brisk walking or jogging, was beneficial to bone development and maintenance 4 through mechanical loading of bone. In addition, brisk walking has been one of the most acceptable exercise programs 5 and can be easily incorporated into an individual's current lifestyle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The high morbidity and mortality of these diseases can intensify both individual and governmental financial burdens. 2,3 In 2010, in a position statement regarding osteoporosis management in postmenopausal women, The North American Menopause Society reported that weight-bearing exercise, which could be as simple as brisk walking or jogging, was beneficial to bone development and maintenance 4 through mechanical loading of bone. In addition, brisk walking has been one of the most acceptable exercise programs 5 and can be easily incorporated into an individual's current lifestyle.…”
mentioning
confidence: 99%
“…The purposes of this study were as follows: (1) to critically evaluate the effects of a walking intervention on BMD at the lumbar spine, at the femoral neck, at the radius, and for the whole body in perimenopausal and postmenopausal women, as reported in RCTs and non-RCTs through systematic review and meta-analysis; and (2) to identify the optimal duration of a walking exercise intervention.…”
mentioning
confidence: 99%
“…The 3% of the Korean population not insured by the KNHIP are either covered by another Medical Aid Program or are temporary or illegal residents. These claims are also reviewed by HIRA, and thus, virtually all information about patients and their medical records is available from the Korean HIRA database, which has been used on several occasions for epidemiological studies [10,11]. In our current study, we used the HIRA database records from January 2007 to December 2011.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the prevalence of dyslipidemia has been shown to be higher in men than in women, with values of 38.4% in 1998 and 54.5% in 2005 [21]. The prevalence of osteoporosis in men is also increasing in South Korea [22]. Some Korean studies have investigated the relationship between osteoporosis and dyslipidemia, but the results were not inconsistent, and they recruited participants only in single university hospitals or health promotion centers [23,24].…”
Section: General Health Behaviorsmentioning
confidence: 99%